Improving Literacy Skill of Eighth-Grade Students through Music-Based Learning Methods - Ubhe, Maria L. Y.; Dopo, Ferdinandus Bate; Fikri, Kanzul; Samino, Sena Radya Iswara (Electronic Journal of Education, Social Economics and Technology, 2024)
This study examines the comprehension skills, information absorption, and critical thinking abilities of middle school students through the implementation of music-based literacy learning (vocal and instrumental). The research subjects were 22 eighth-grade students from Class VIII A at SMP Negeri 4 Bajawa, Ngada Regency, East Nusa Tenggara Province, consisting of 12 male and 10 female students. The research employed a classroom action research method using the McTaggart Kemmis Nixon model, which involves two cycles comprising four stages: planning, action, observation, and reflection. In the pre-cycle phase, students' literacy skills averaged 51.59. After implementing the intervention in Cycle I, their average literacy skills increased to 62.5. Further improvement was observed in Cycle II, where the average literacy score reached 74.09. The results from each cycle indicate consistent improvement in students' literacy skills. As a result, music-based literacy learning (vocal and instrumental) effectively enhances students' abilities in reading comprehension, information absorption, expressing opinions, and critical thinking in middle school.